TECHNOLOGY TREND OF DIGITAL IDENTITY: A BIBLIOMETRIC APPROACH - Tika Riskawati; Suryanegara, Muhammad (Informatika, Universitas Jenderal Soedirman, 2024)
The future of digital ecosystem requires various supporting technologies, one of which is digital identity. A necessary validation tool not only for individuals but also for organizational institutions which later will be used in digital economic activities. Indonesia as a country with large citizen urgently needs digital identity to protect the people and to upheld national security systems. However, we need to figure out the overall development of digital identity before adopting the technology. This article conducts a bibliometric analysis to investigate the future that digital identity holds. The investigations revealed that digital identity will eventually evolve to four technologies such as decentralized identity, verifiable credentials, self-sovereign identity, and metaverse. The findings will be a catalyst for the information technology and telecommunications industry to adopt digital identity technology.